Knowledge and the future school : curriculum and social justice - Young, Michael F. D.; Lambert, David, 1976- (New York : Bloomsbury Academic, 2014)
"Written at a time of uncertainty about the implications of the English government's curriculum policies, Knowledge and the Future School engages with the debate between the government and large sections of the educational community. It provides a forward-looking framework for head teachers, their staff and those training teachers to use when developing the curriculum of individual schools in the context of a national curriculum. While explaining recent ideas in the sociology of educational knowledge, the authors draw on Michael Young's earlier research to distinguish three models of the curriculum in terms of their assumptions about knowledge, referred to in this book as Future 1, Future 2 and Future 3. They link Future 3 to the idea of 'powerful knowledge' for all pupils as a curriculum principle for any school, arguing that the question of knowledge is intimately linked to the issue of social justice and that access to 'powerful knowledge' is a necessary starting point for the education of all pupils. Knowledge and the Future School offers a new way of thinking about the problems that head teachers, their staff and curriculum designers face. In charting a course for schools that goes beyond current debates, it provides a perspective that policy makers should not avoid"--
"Written at a time of uncertainty about the implications of the Coalition government's curriculum policies, Knowledge and the Future School engages directly with the debate between English government and large sections of the educational community. It provides a forward-looking framework for head teachers, their staff and those training teachers to use in their work developing the curriculum of individual schools in the context of a national curriculum. Knowledge and the Future School is the first book that explains recent ideas in the sociology of educational knowledge to a professional audience of school leaders and classroom practitioners. Michael Young draws on his earlier research to distinguish three models of the curriculum in terms of their assumptions about knowledge, referred to in this book as Future 1, Future 2 and Future 3. He links Future 3 to the idea of 'powerful knowledge' for all pupils as a curriculum principle for any school, arguing that the question of knowledge is intimately linked to the issue of social justice and that access to 'powerful knowledge' is a necessary starting point for the education of all pupils. Knowledge and the Future School is not a handbook. But neither is it just another book of educational theory. It offers a new way of thinking about the problems that head teachers, their staff and curriculum designers face. In charting a course for schools that goes beyond current debates, it provides a perspective that policy makers will be unable to avoid"--
Machine generated contents note: -- Preface: Why should you read this book? Martin Roberts (The Prince's Teaching Institute, UK) and Carolyn Roberts (Thomas Tallis School, UK)Introduction, Michael Young (Institute of Education, UK) and David Lambert (Institute of Education, UK), Carolyn Roberts (Prince's Teaching Trust, UK) and Martin Roberts (The Prince's Teaching Institute, UK)1. Knowledge, curriculum and the future school, Michael Young (Institute of Education, UK)2. Why curriculum? Michael Young (Institute of Education, UK)3. Powerful Knowledge as a curriculum principle, Michael Young (Institute of Education, UK)4. The progressive case for a subject-based curriculum Michael Young (Institute of Education, UK)5. Curriculum change and control: a Headteacher's perspective, Martin Roberts (The Prince's Teaching Institute, UK)6. Curriculum leadership and the knowledge-led school, Carolyn Roberts (Thomas Tallis School, UK)6. Subject teachers in knowledge-led schools, David Lambert (Institute of Education, UK)7. Afterword, Michael Young (Institute of Education, UK), David Lambert (Institute of Education, UK), Carolyn Roberts (Thomas Tallis School, UK) and Martin Roberts (The Prince's Teaching Institute, UK)BibliographyIndex.
Keywords: Education -- Curricula -- Great Britain; EDUCATION / General; EDUCATION / Leadership; EDUCATION / Curricula